2019
DOI: 10.1108/ejim-12-2018-0255
|View full text |Cite
|
Sign up to set email alerts
|

Honor the old, welcome the new: an account of unlearning and forgetting in NPD teams

Abstract: Purpose The purpose of this paper is to empirically investigate the antecedents, levers of control and outcomes of organizational unlearning and forgetting in new product development (NPD) teams. Design/methodology/approach This paper employs a holistic multiple-case study design. This paper gathered data from 30 individual semi-structured interviews in 10 different NPD teams as well as additional data to triangulate the findings. Findings The authors propose a model of unlearning and forgetting elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
0
21
0
2
Order By: Relevance
“…Conceptualizations of strategic problem formulation, for instance, proposed that during reorientation periods, unlearning was vital because contextual discontinuities triggered secondorder learning and involved changes in decision-making premises and assumptions, requiring unlearning of prior modes of organizing such as practices and routines and increasing behavioral variability (Lyles and Thomas, 1988). This view was confirmed by studies of contractor organizations in Hong Kong that found a correlation between unlearning and double-loop learning (Argyris and Schön, 1978) to help change previous assumptions, beliefs, and routines that had caused errors and to support subsequent learning processes (Wong et al, 2012 (Bridoux et al, 2013; see also Klammer and Gueldenberg, 2019b). This transition period was proposed to build upon three connected processes of initial routine destabilization: ongoing discarding-from-use of old behaviors; experimenting with new behaviors; and discharge of prior understanding to develop new understanding (Fiol andO'Connor, 2017a, 2017b).…”
Section: Processes and Toolsmentioning
confidence: 91%
See 1 more Smart Citation
“…Conceptualizations of strategic problem formulation, for instance, proposed that during reorientation periods, unlearning was vital because contextual discontinuities triggered secondorder learning and involved changes in decision-making premises and assumptions, requiring unlearning of prior modes of organizing such as practices and routines and increasing behavioral variability (Lyles and Thomas, 1988). This view was confirmed by studies of contractor organizations in Hong Kong that found a correlation between unlearning and double-loop learning (Argyris and Schön, 1978) to help change previous assumptions, beliefs, and routines that had caused errors and to support subsequent learning processes (Wong et al, 2012 (Bridoux et al, 2013; see also Klammer and Gueldenberg, 2019b). This transition period was proposed to build upon three connected processes of initial routine destabilization: ongoing discarding-from-use of old behaviors; experimenting with new behaviors; and discharge of prior understanding to develop new understanding (Fiol andO'Connor, 2017a, 2017b).…”
Section: Processes and Toolsmentioning
confidence: 91%
“…This transition period was proposed to build upon three connected processes of initial routine destabilization: ongoing discarding-from-use of old behaviors; experimenting with new behaviors; and discharge of prior understanding to develop new understanding (Fiol andO'Connor, 2017a, 2017b). Research also proposed that temporal and spatial freedom could help identify outdated knowledge and facilitate unlearning practices (Klammer and Gueldenberg, 2019b).…”
Section: Processes and Toolsmentioning
confidence: 99%
“…Finally, we selected four final cases based on two criteria: (a) the case clearly described the unlearning process, and (b) the case showed unlearning at one or more levels: individual, group, organizational, or combined level. The four cases were conducted in diverse sectors (construction, healthcare, public service, and R&D) in different countries (Austria, Australia, Brazil, Germany, Liechtenstein, Spain, and Switzerland) (Cegarra‐Navarro, Wensley, & Polo, ; Klammer & Gueldenberg, ; Love, Smith, & Teo, ; Wilbert, Durst, Ferenhof, & Selig, ).…”
Section: Methodsmentioning
confidence: 99%
“…In this section, we introduce four cases that demonstrate the unlearning process in each organization (Cegarra‐Navarro et al, ; Klammer & Gueldenberg, ; Love et al, ; Wilbert et al, ). For each case, we summarize the organizational context related to unlearning and how unlearning has been implemented based on the three phases of the unlearning process: awareness, relinquishing, and relearning.…”
Section: Unlearning Casesmentioning
confidence: 99%
“…If we want to create trust, if we're going to succeed, then we must start with ourselves. Self-leadership will become the most important capability in a digital economy because you have to manage processes of unlearning your old mindsets and learning new leadership skills (Klammer and Güldenberg 2019).…”
Section: From Leading Others Toward Leading Yourselfmentioning
confidence: 99%